Makna Kompensasi Dalam Perspektif Keberlangsungan Hidup (Studi Kasus Motivasi dan Kompensasi Satuan Pekerja Keamanan Outsourcing pada PT Pesonna Optima Jasa Di Sleman Yogyakarta) - Kundarti, Fitria Kundarti; Rini, Ika Tirta Candra; Setiawati, Trias Setiawati (Journal Competency of Business, 2022)
The development of the world of work is growing so rapidly with the outsourcing work system. The outsourcing system is a work system that uses the services of a power expert in managing a particular job or project. There are some negative perceptions from the public about the status of outsourced employees because they are considered to have lower compensation rights and there is no guarantee of career certainty and employment status in the long term. In addition, the number of complaints and dissatisfaction with receiving compensation for outsourcing employees, directly or indirectly can affect work motivation. This study focuses on the motivation and compensation of the Outsourcing Security Worker Unit at PT Pesonna Optima Jasa in Sleman Yogyakarta entitled "The Meaning of Compensation in the Perspective of Survival". The purpose of this research is to find out: 1. perceptions of outsourcing work and compensation, 2. employee motivation and reasons for staying as outsourced employees. In this study, the authors used qualitative research methods with a case study approach and data collection methods in the form of interviews and documentation. Speakers are seven people. Test the validity of the data, test transferability and test credibility. The data testing method is data triangulation, data analysis is reduction, data presentation and conclusion drawing. The results of the study conclude that firstly, employee welfare has an important role in creating employee motivation to work and the influence of the amount of compensation to meet needs with workload and responsibility given to employee motivation and performance. Second, there is intrinsic motivation from employees to realize their desires, namely being able to fulfill their life needs and there is to realize their desires, namely being able to fulfill their daily needs and extrinsic motivation, namely companies that provide compensation in the form of salaries as a reason to still survive outsourcing staff/employees other than that, do not get the opportunity. in other jobs, although the income of outsourced employees is still far from feasible and not commensurate with the responsibilities given, this results in a decrease in employee motivation.